Effects of Different LED Light Recipes and NPK Fertilizers on Basil Cultivation for Automated and Integrated Horticulture Methods - Silvia Barbi; Francesco Barbieri; Alessandro Bertacchini; Luisa Barbieri; Monia Montorsi (Applied Sciences, 2021)
This study aims to optimize the conditions for “Genovese” basil (Ocimum Basilicum) germination and growth in an indoor environment suitable for horticulture through a synergic effect of light and fertilizers addition. In fact, several studies determined that specific light conditions are capable of enhancing basil growth, but this effect is highly dependent on the environmental conditions. In this study, the effect of different light sources was determined employing a soil with a negligible amount of fertilizer, demonstrating substantial improvement when light-emitting diode (LED) lights (hyper red and deep blue in different combinations) were applied with respect to daylight (Plants height: +30%, Total fresh mass: +50%). Thereafter, a design of experiment approach has been implemented to calculate the specific combination of LED lights and fertilizer useful to optimize the basil growth. A controlled-release fertilizer based on nitrogen, phosphorus, and potassium (NPK) derived from agro-residues was compared with a soil enriched in macronutrients. The results demonstrate significant improvements for the growth parameters with the employment of the controlled-release NPK with respect to enriched soil combined with a ratio of hyper red and deep blue LED light equal to 1:3 (Total fresh mass: +100%, Leaves number: +20%).